After Quarantine: The Future of Screendance - Omari 'Motion' Carter; Sandra Maduoma; Antoine Marc; Vilma Tihil; Alice Underwood; James Williams (The International Journal of Screendance, 2021)
No abstract available.
Keywords: Covid-19; screendance; film; dance film; future; translation; image; collaboration; education; online; digital; access